A behavior of a class of ξ(s)-QSO in dimension 2 - Mukhamedov, Farrukh; Saburov, Mansoor; Qaralleh, Izzat (2012)
In this paper, we gave classifications of ξ(s)-quadratic stochastic operators (in short QSO) in 2D simplex and studied asymptotic behaviors of some classes of ξ(s)-QSO.